2018
DOI: 10.3892/mmr.2018.9184
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effects of microRNA‑184 on osteosarcoma via the Wnt/β‑catenin signaling pathway

Abstract: The present study aimed to investigate the role of microRNA (miRNA/miR)-184 in osteosarcoma growth, development and metastasis, and the effects of miRNA-184 on the proliferation, invasion and metastasis of osteosarcoma cells and associated mechanisms. In vitro, miR-184 was transfected into U-2OS cells and 143B cells. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression of miR-184. MTT was utilized to detect cell proliferation. A Transwell assay was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The rno‐miR‐184 has dual functions in cancers. It is an onco‐miRNA in osteosarcoma (Du, Li, Wang, Huang, & Xu, ), squamous cell carcinoma of tongue (Wong et al, ), but acts as a tumour suppressor in colorectal cancer (Wu, Liu, Wu, Wu, & Yao, ), breast cancer (Fu et al, ), even acts as both onco‐miRNA (Wu et al, ) and suppressor miRNA in glioma (Cheng et al, ). Although rno‐miR‐184 is an onco‐miRNA in prostate cancer (Lin, Chiang, Chang, & Ying, ; Walter, Valera, Pinto, & Merino, ), there is no evidence about relationship between rno‐miR‐184 and BPH.…”
Section: Discussionmentioning
confidence: 99%
“…The rno‐miR‐184 has dual functions in cancers. It is an onco‐miRNA in osteosarcoma (Du, Li, Wang, Huang, & Xu, ), squamous cell carcinoma of tongue (Wong et al, ), but acts as a tumour suppressor in colorectal cancer (Wu, Liu, Wu, Wu, & Yao, ), breast cancer (Fu et al, ), even acts as both onco‐miRNA (Wu et al, ) and suppressor miRNA in glioma (Cheng et al, ). Although rno‐miR‐184 is an onco‐miRNA in prostate cancer (Lin, Chiang, Chang, & Ying, ; Walter, Valera, Pinto, & Merino, ), there is no evidence about relationship between rno‐miR‐184 and BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Of the group of 18 upregulated miRNAs (Let-7c, Let-7d, Let-7e, Let-7f, miR-135b, miR-221, miR-184, miR-18a-5p, miR-200, miR-1, miR-9, miR-744, miR-296-5p, miR-199a-3p, miR-320, miR-654, miR-141-3p and miR-369-3p), only miR-1, Let-7d, miR-320, miR-221, miR-184, miR-141-3p, miR-18a-5p, miR-135b, Let-7a, miR-199a-3p, miR-365, and miR-744 had been investigated [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ] in OS before now.…”
Section: Discussionmentioning
confidence: 99%
“…miR-184 has been described to be closely related to tumor occurrence and progression in several tumors [ 97 , 98 ], among which OS. Du Z. et al, investigating the role of miR-184 in OS cell lines, have demonstrated that miR-184 is responsible for an abnormal cellular proliferation by upregulating Wnt and β-catenin mRNA expression levels [ 69 ]. Yin G. et al reported that miR-184 is highly expressed in OS cell lines and demonstrated that the inhibition of this leads to a suppression of cell proliferation [ 72 ], confirming the oncogene behavior of this miRNA, as has been described in other malignant tumors [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that Wnt signaling pathway plays an important role in the development of osteosarcoma. Du et al, [ 44 ] found that inhibition of miRNA- 184 may reduce tumor volume of osteosarcoma by regulating the Wnt /β- catenin signaling pathway. Zhang et al, [ 45 ] suggested that miR-107 inhibit development of osteosarcoma via the Wnt signaling pathway, and the critical role of miR- 214 in human osteosarcoma also through involving the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%